Navigating the Startup Innovation Ecosystem: Strategies for Effective External Resource Management - Gautam, Prakash Kumar; Gautam, Sushmita (The Batuk, 2024)
This research examines how innovation ecosystems facilitate startup innovation across the creation, development, and market phases. We analyze the roles of diverse ecosystem actors, emphasizing their contributions to resource dynamics using the case method approach. Semi-structured interview-based data was analyzed using content analysis. The study revealed the significance of the strategy of using external resources for the success of startups. During the creation phase, non-market-oriented entities like universities and incubators support startups with crucial early-stage R&D funding and business model formulation. In the development phase, startups refine their products with backing from accelerators, investors, and customers, utilizing innovation resources for prototyping and validation, and transitioning into the market phase, startups scale operations with market-oriented actors, focusing on organizational readiness and leveraging established business models for growth. Throughout these phases, startups balance exploration and exploitation strategies, enabling innovation ambidexterity. Our findings highlight how innovation ecosystem actors provide essential resources—physical, social, financial, and human—that foster startup resilience and maturity. Grounded in the Resource-Based View framework, this study offers empirical insights into strategic adaptations within innovation ecosystems, illustrating their transformative impact on startup success.<